Perancangan Sistem Kasir pada Toko Grosir Bu Yanti - Inta Nalurina Amerta; Shafa Yashinta Agustina; Ririn Rahmawati; Tinuk Agustin (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
: Current technological developments that are increasing can have a positive impact on SMEs. At wholesale egg shops, they still use a manual cashier system with only being recorded in large books, so the service is less than optimal and less accurate. So it is not uncommon for customers to be disappointed in payment and refund services. By doing this research, it is hoped that it will be able to create a cashier system that runs at egg grocery stores that is able to increase cashier performance efficiency.